Effect of a yogic stress management technique (cyclic meditation) on stress, mindfulness, and well-being: A systematic review - K. Ranisha; Sony Kumari (Yoga-Mimamsa)
Cyclic meditation (CM) is a unique form of guided meditation that alternates between yoga postures and relaxation techniques to achieve a state of deep relaxation. Originating from ancient yogic wisdom and developed by SVYASA University, CM has gained popularity as an effective method for stress management and overall well-being which can be practiced by even beginners to induce the meditative state. This systematic review aims to fill this gap by summarizing peer-reviewed studies on CMs impact on stress and well-being. The authors conducted a systematic review following the PRISMA guidelines to summarize the evidence of CM for recommending it as a well-being practice or an intervention for stress and related health problems. Electronic databases (PubMed, SCOPUS, CNKI, and Google Scholar) were searched for peer-reviewed studies related to CM that reported at least one outcome of stress and well-being in the diverse populations. The search was limited to papers published in the English language and published between 2006 and 2022. A search yielded 109 results. In all, 16 papers were considered for the review. Studies demonstrated a significant reduction in stress levels and improvement in well-being. The review showcased the positive effect of CM, and the quality of the studies was consistent; however, more high-quality randomized controlled trials with the long-term follow-ups are needed to confirm the result in the clinical and nonclinical populations.